MIGA roundtable on foreign direct investment policies in Africa : proceedings and lessons - Bachmann, Heinz; Kwaku, Ken (Washington, D.C. : World Bank, 1994)
This research papers contains some of the important views of participants on the need to provide a road map for African countries on how to attracts foreign investors into their countries.
asm; 24/01/19
Loans
Keywords: Investments, Foreign